Current behavior analysis of the single supply differential capacitive sensing - Che Mustapha, Nurul Arfah; Alam, A. H. M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (Institute of Electrical and Electronics Engineers Inc., 2017)
Differential capacitive sensing technique has gained popularity in capacitance measuring system due to its high symmetrical implementation, easy to be implemented using discrete components and has a characteristic of high linearity in its system. However, very few work has reported on the differential CVC system that is able to operate at a high frequency operation especially when using discrete method. In this work, a differential CVC is proposed using discrete single supply, suitable for energy harvesting and WSN application. The method has emphasised on the rectifier current behavior analysis of the capacitive sensing circuit. Using this method, sensitivity of 0.04933 mV per 1 ƒF capacitance change is achievable with low power consumption of 3.83 mW. The proposed method has also shown high linearity of R-squared value 0.99788 between 5 and 9.5 pF capacitance change. Finally, the recorded DC output voltage is in the range of 1.6505 to 1.8725 V output with working frequency of 200 kHz operation.